2014
DOI: 10.3390/molecules19032829
|View full text |Cite
|
Sign up to set email alerts
|

Chiroptical Properties and the Racemization of Pyrene and Tetrathiafulvalene-Substituted Allene: Substitution and Solvent Effects on Racemization in Tetrathiafulvalenylallene

Abstract: Dissymmetric 1,3-diphenylallene derivative 3 connected with 4,5-bis(methylthio)tetrathiafulvalenyl and 1-pyrenyl substituents was prepared and characterized. The molecular structure was determined by X-ray crystallographic analysis. Optical resolution was accomplished using a recycling chiral HPLC, and its chiroptical properties were examined with optical rotation and electronic circular dichroism (ECD) spectra. The title compound underwent photoracemization under daylight. This behavior was investigated in va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…We monitored a change in the spectrum of ( M )- 2a with time at a constant temperature (Figure a,b) and found that the molar CDs continuously decreased to give a spectrum close to the steady state. On the basis of a change in the molar CD at 319 nm, which was observed in the initial state, we plotted a value of ln (Δε/Δε 0 ) versus time t and found a process that obeyed first-order kinetics [rate constant k /s –1 = 1.2 × 10 –5 (293 K), 1.9 × 10 –5 (298 K), and 3.4 × 10 –5 (303 K)] (Figure c,d). ,, On the basis of these data, the activation energy Δ G ⧧ for the interconversion between two pseudo enantiomeric forms with ( M )- or ( P )-helicity was estimated to be 77 kJ mol –1 .…”
Section: Results and Discussionmentioning
confidence: 95%
“…We monitored a change in the spectrum of ( M )- 2a with time at a constant temperature (Figure a,b) and found that the molar CDs continuously decreased to give a spectrum close to the steady state. On the basis of a change in the molar CD at 319 nm, which was observed in the initial state, we plotted a value of ln (Δε/Δε 0 ) versus time t and found a process that obeyed first-order kinetics [rate constant k /s –1 = 1.2 × 10 –5 (293 K), 1.9 × 10 –5 (298 K), and 3.4 × 10 –5 (303 K)] (Figure c,d). ,, On the basis of these data, the activation energy Δ G ⧧ for the interconversion between two pseudo enantiomeric forms with ( M )- or ( P )-helicity was estimated to be 77 kJ mol –1 .…”
Section: Results and Discussionmentioning
confidence: 95%
“…Although the reason for the amplified CD was not clearly stated in this paper, it is understood that the arrangement of the transition dipole moments (magnetic and electric) resulting from the symmetrical structure enhanced the chiroptical properties because of the selection rule in a certain electronic transition. We have also reported several acyclic chiral compounds with C2-symmetric tetrathiafulvalene (TTF) connected to allenes (2), [13][14][15] [2.2]paracyclophane ([2.2]PC) (3), 16 and spiro carbons (4); 17 these compounds exhibit chiroptical and redox properties (Figure 1b). The oxidized species of these compounds are all stable, and the electronic spectra including CD were measured.…”
Section: Synlett Account / Synpactsmentioning
confidence: 99%
“…In contrast, several allenes directly connected with electron-donating groups occasionally underwent photoracemization [ 12 13 ]. Although the mechanism of the photoracemization is not clear, a comparative examination of the racemization rate in 1 and 2 , the latter of which is a dissymmetric allene having a TTF and a pyrenyl group at 1,3-position, suggests that the direct connection of the TTF units may strongly affect the fast racemization [ 14 ]. From this point of view, we decided to employ a 1,3-diphenylallene derivative ( 3 ) as a stable chiral framework.…”
Section: Introductionmentioning
confidence: 99%